Epidemiology of MTP in a tertiary care center over a period of 3 years - Sharma, Bhawna; Saxena, Namrata; Sharma, Anshu; Arora, Neetu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Medical termination of pregnancy was legalized in India under the MTP act of 1971 which states that all the women can legally have an abortion up to 20 weeks of gestation if indicated. This study is a retrospective analysis of incidence, indication, the age group availing the facility, socio-demographic and obstetric profile of MTP seekers and the method of contraception followed after MTP. Methods: A retrospective 3-year data was analyzed by MTP register of the hospital as a reference. Results: The incidence rate of MTP is 96/1000 live births in the institute. The main reason for MTP is failure of contraception which highlights the unmet need of contraception and counselling. Majority of the age group availing MTP belonged to 16-20 years. Most of the women were from urban slums, were illiterate and belonged to class IV and V according to Prasad’s classification. Mostly MTP seekers were parous, having ≥2 living children, and maximum no. of them went to private hospitals for their previous MTP. Medical method was the most favoured method of the care giver as well as of the patient. OCP was the choice of contraception after MTP. Religious difference is still very evident in availing MTP services which can be minimized by tactful counselling. Conclusion: MTP act of 1971 opened new horizons for the unwanted pregnancies. Young population opting for MTP indicates the unmet need of contraception and counselling suggesting that implementation and integration of MTP services should be at the root level.